Tested, trusted, yet frustrating: an investigation into the effectiveness of environmental radio in Oyo State Nigeria (2005)
"Radio stations have used jingles for environmental education and communication in Nigeria for decades though not much has been done to study the impact of such use—which is the purpose of this article. Through 12 focus group discussions (FGDs) in six local government areas of Oyo state, Nigeria, interviews with the program directors of two radio stations, and a questionnaire administered with 18 program producers from the stations, the researcher found that producers and directors had full confidence in the ability of the jingles to engender environmental sanctity, and that listeners fully understood the message of the jingles. However, listeners mostly did not adopt the behavior recommended by the jingles, because the government did not make the infrastructures needed to do so available or functional. Though the jingles were aired, the outcome of their use is a frustration of the listeners and even the producers. Based on the findings, the article draws five lessons for better social marketing of environmental behavior. "